Unsteady forces on a hand in swimming in impulsive start configuration - Samson, M.; Bernard, A.; Monnet, T.; Lacouture, P.; David, L. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
Competitive swimming aims to achieve high performances by the only mechanical action of the swimmer in the fluid at rest. The cyclic action of the arms and legs generates a flow which, by the principle of reciprocal actions (Newton`s 3rd law) acts on the body surfaces. In this context, the hand movement is crucial. The hand propulsive forces directly depend on this flow. Study of these propulsive forces have made mostly from quasi-steady approaches (Schleihauf 1979), and results are commonly given in the form of lift (CL) and drag (CD) coefficients.